2011
DOI: 10.1007/s10570-011-9583-2
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole (PPy) chemical synthesis with xylan in aqueous medium and production of highly conducting PPy/nanofibrillated cellulose films and coatings

Abstract: Polypyrrole was chemically synthesised by using, for the first time, Birchwood xylan as additive, and ammonium peroxydisulfate (APS) as oxidant. The impact of additive concentration, polymerisation time and reagents concentration on PPy conductivity was studied. It was shown that, once fixed the pyrrole (Py)/ APS and Py/xylan optimal ratios, the best conductivities (26 S/cm) were obtained for short polymerisation times (30 min) and increased reactants concentration. Morphological analysis of PPy particles, Py … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…Also their surfaces are smoother, which can be important, e.g., for high definition of linewidths in printed devices. Nanopapers can be furnished also by a wealth of other functional properties, like barrier properties to reduce vapour permeation, fire‐retardancy, magnetic properties, and electrical conductivity . Among the potential applications, we foresee that nanopaper device substrates for flexible transparent devices are particularly promising.…”
Section: Functional Materials Based On Nanocellulosesmentioning
confidence: 99%
“…Also their surfaces are smoother, which can be important, e.g., for high definition of linewidths in printed devices. Nanopapers can be furnished also by a wealth of other functional properties, like barrier properties to reduce vapour permeation, fire‐retardancy, magnetic properties, and electrical conductivity . Among the potential applications, we foresee that nanopaper device substrates for flexible transparent devices are particularly promising.…”
Section: Functional Materials Based On Nanocellulosesmentioning
confidence: 99%
“…It is also possible that the difference in molecular weights of synthesized polyaniline (at different preparation conditions) contribute to the differences in thermal properties. This behaviour was also observed for DBSA-doped polyaniline nanoparticles prepared by reverse micelle polymerization at different DBSA concentrations, 31 and for other conducting polymeric systems such as polypyrrole, 32 where the authors reported that further insertion of dopant molecules within PPy chains created a steric barrier for the charge carrier movement between PPy particles. The interdependence between CNCs concentration and conductivity of the nanocomposite films is explored in Fig.…”
Section: Thermal Properties Of Cncs-pani-dbsa Nanocomposite Filmsmentioning
confidence: 64%
“…Conducting polymers have drawn great attention because of their useful electrical and optical properties which are mainly governed by the delocalized π‐electrons and dopants in the polymer backbone . Additionally, light weight, flexibility, scalable synthesis, and facile processability enable conducting polymers to emerge as an ideal candidate for versatile applications such as wearable electronics, flexible displays, photovoltaics, and so on . Polypyrrole (PPy) is one of the most intensively studied conjugated polymers .…”
Section: Introductionmentioning
confidence: 99%